Maintenance Tasks for 20 Kv Medium-Voltage Switchgear Based on Technical Judgment Experience and Manufacturer - Soetadji, Prabowo; Sutikno , Tole; Fadlil , Abdul (Newinera Publisher, 2024)
A 20 kV medium-voltage switchgear is an important equipment in the electricity system that distributes electricity generated by the 20 kV electric power generator to electricity users. Calor Emag, Merlin Gerin, Alsthom, Fuji, AEG, Schneider, Meidensha, Goldstar, Modalek, Areva, and Siemens are among the companies that make products. This study describes a method for maintaining 20 kV medium-voltage switchgear, an essential equipment in the electricity system. In less technical terms, the failure rate is high at the beginning of an asset's life, which follows the curve of the bathtub. However, the failure rate quickly declines as we identify and discard defective components and eliminate early sources of potential failures, such as installation errors. This study introduces a novel approach by examining the relationship between maintenance tasks, which are based on technical judgment and experiences, and the maintenance tasks provided by the manufacturer for 20 kV medium voltage switchgear. The goal is to develop and deliver the most effective maintenance method for 20 kV medium voltage switchgear, to prevent malfunctions or even catastrophic explosions, while maintaining the lowest possible maintenance costs. Total use of labor over 2 years (24 months) for daily, monthly, 3 monthly, and 2 yearly is 3554-man hours (MH). It provides a comprehensive approach to preventing malfunctions and explosions, resulting in optimal maintenance costs and performance.